What Makes Professional Development Coherent? Uncovering Teacher Perspectives on a Science Literacy Project. (2nd November 2017) - Kohnen, Angela M.; Whitacre, Michelle P.
ABSTRACT: In this study, the authors sought to uncover the characteristics of professional development (PD) that were identified by teacher-participants as being important to their implementation of project ideas. Using phenomenological interviewing, the authors talked with nine teacher-participants about changes to their teaching practices after they participated in a university-based PD program focused on science literacy. Findings indicate that teachers benefited from immersion in authentic practices with an expert facilitator, a clear definition of science literacy that challenged teachers' previous understandings, and ongoing contact with a community of like-minded educators for collaboration and recognition. Findings confirm previous research and expand our understanding of the concept of "coherence" in professional development.